Pendugaan Parameter Genetik Sifat Pertumbuhan Sapi Bali di BPTU HPT Denpasar - Setiyabudi, R. J. W.; Muladno, Muladno; Priyanto, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Breeding Center of Bali Cattle in Bali has applied Village Breeding Center (VBC) Program which an area of farmer belonging to groups that develop breeding program. These farms are expected to act as nuclei in open nucleus schemes, where superior animals are multiplied at Breeding Center (nucleus), distributed to farmers, andthe best animals from the farmers are brought back to the central farm for further breeding. This study was to estimate non-genetic and genetic of growth traits consisting of birth (BW), weaning (WW), and 12 months (YW) weight. This study used pedegree record of Breeding Center from 2008 to 2013 years. The number of sapi Bali used to determine growth traits of BW, WW, and YW were 573; 541; and 523 heads, respectively.Data were analyzed using General Linier Model (GLM) to identify non-genetic. Estimation of genetic including heritability, repeatability, genetic and phenotypic correlation were calculated using General Linier Model and Restricted Maximum Likelihood. Genetic and phenotypic trends were calculated using the regression mean breeding values on birth year.Heritability values were 0.02±0.08; 0.83±0.18 and 0.62±0.30for BW, WW and YW, respectively. The higest correlation showed between WW and YW for genetic and fenotipic were 0.719 and 0.650, respectively. The regression estimates on various trends of EBV and phenotipic trends for WW and YW showed no deinite trendsince the regression equation was not signiicant (P>0.01) and R2 was relatively low, but the phenotypic trends of BW showed constant decrease (P<0.01). The results obtained in the present study realized that one signaling to the programthat need for evaluated in selection and or management procedure in the scheme